Comprehensive Assessment of the Risk of Symptomatic Embolism in Patients With Infective Endocarditis - Sebastian D. Santos‐Patarroyo; Juan A. Quintero‐Martinez; Brian D. Lahr; Supavit Chesdachai; Daniel C. DeSimone; Hector R. Villarraga; Hector I. Michelena; Larry M. Baddour (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Echocardiographic evaluation of vegetations is crucial in infective endocarditis (IE). Although several studies have noted a link between larger vegetations and an increased risk of embolization, a more comprehensive evaluation of vegetation characteristics in a contemporary cohort has not been conducted. Our study aimed to define the short‐term risk of symptomatic embolization in patients with IE. Methods and Results The Mayo Clinic IE registry was screened to identify patients from 2015 to 2021 who had undergone transesophageal echocardiography. Multivariable subdistribution hazards regression analysis was used to identify factors associated with the cumulative incidence of symptomatic embolism over 30 days accounting for the competing risk of death. Overall, 779 patients with IE were included, of whom 517 (66.4%) were men, median age was 65.0 (interquartile range, 52.9–74.8) years, and 89.3% were White. In total, 234 patients had a symptomatic embolic event, a 30‐day cumulative incidence of 30.2%. In multivariable analysis, a highly mobile vegetation was the strongest predictor of embolism (P<0.001). Vegetation length with interaction of IE type was also associated with embolic risk (P<0.001), with a stronger effect in native valve IE (P interaction=0.001). Other associated factors included multiple vegetations, younger age, and Staphylococcus aureus. A nomogram that incorporated these factors was constructed to facilitate the prediction of embolic risk. Conclusions Highly mobile, larger vegetations are associated with embolic events. Embolic risk could be assessed by evaluating length as a continuous variable, alongside other echocardiographic findings, using a newly developed scoring tool; external validation is warranted.